Romantic drama of Sandhyakala ning Majapahit by Sanusi Pane and its implications for literary learning in senior high school - Ni Wayan Ayu Permata Sari*) (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This study aims to reveal the romanticism contained in Sandhyakala ning plays Majapahit works Sanoesi Pane. The method used adallah descriptive qualitative content analysis techniques. The results of this study stated that plays Sandhyakala ning Majapahit works Sanoesi Pane contains romanticism. The third characteristic of romanticism analyzed, namely awareness of wild nature, the uniqueness and distinctiveness of the individual and the longing for the presence of a social order that is warm, everything depicted in the play. In the play, parts 1 and 2 illustrate the awareness of the wild. Then, sections 2 and 3 illustrate the uniqueness and distinctiveness of the individual. Sections 3, 4, and 5 describe a longing for the presence of a social order that is warm. The attitude shown through dialaog and characters in the text of the characteristics of romanticism. So, script Sandhyakala ning Majapahit is told through the flow of romanticism. The implications of this research for the study of literature in high school is as an alternative material of literary learning materials.